Deubiquitinating enzymes as novel anticancer targets. (April 2007) - Nicholson, Benjamin; Marblestone, Jeffrey G; Butt, Tauseef R; Mattern, Michael R
Tagging proteins with mono- or poly-ubiquitin is now recognized as a multifaceted and universal means of regulating cell growth and physiology. It does so by controlling the cellular lifetime of nearly all eukaryotic proteins and the cellular localization of many critical proteins. Enzymes of the ubiquitin pathway add (ligases) or remove (deubiquitinases [DUBs]) ubiquitin tags to or from their target proteins in a selective fashion. Similarly to the kinases and their corresponding phosphatases, ubiquitin ligases and DUBs have become actively studied molecular oncology targets for drug discovery. Approximately 79 functional DUBs exist in the human proteome, suggesting that selective intervention is a reasonable therapeutic objective, with the goal of downregulating or ablating oncogene products or, alternatively, upregulating or sparing tumor suppressors. In the following review, this fascinating class of regulatory enzymes will be described, and specific examples of DUBs that are viable targets for anticancer therapy will be considered.